The Philippine Islands, 1493-1898 explorations by early navigators, descriptions of the islands and their peoples, their history and records of the Catholic missions, as related in contemporaneous books and manuscripts, showing the political, economic, commercial and religious conditions of those islands from their earliest relations with European nations to the close of the nineteenth century, Volume 16, 1609 - Blair, Emma Helen d.1911., ed.; Robertson, James Alexander 1873-1939; Bourne, Edward Gaylord 1860-1908; iGLibrary (online resource). ([Cleveland, O The A.H. Clark Company, 1907)
The documents presented in this volume (which covers the years 1728-59) form a comprehensive and interesting survey of the islands and their condition-social, religious, military, and commercial - during the middle portion of the eighteenth century; and the writers of these are prominent in their respective spheres of action. The appendix furnishes a valuable description of the savage Zambals of western Luzon, written by a Dominican missionary among those people in 1680.
Electronic Reproduction.
Keywords: Demarcation line of Alexander, VI; Missions -- Philippines; Electronic books; Philippines -- History -- Sources; Philippines -- Discoveries and explorations